The Lost Garden of Aceh - Muhammad Naufal Fadhil; Nurul Fakriah (Journal of Architecture & Environment, 2021)
In the seventeenth century AD, the Sultanate of Aceh under the leadership of Sultan Iskandar Thani made a manuscript entitled Bustanussalatin. This manuscript contains the story of the creation of the universe, the relationship between God and man, the lineage of the sultans of Aceh, as well as a small section about the royal garden called Taman Ghairah. The existence of this garden is still questionable, but scholars who research this garden associate three buildings nearby the former royal palace as a remnant of this Garden. This paper questions whether this garden was built or not and when it was built and the loss of this garden. Through literature review and archival research, this paper tries to trace the presence and disappearance of this garden. The Bustanussalatin manuscript provides information on the development of this garden during the reign of Iskandar Thani. Meanwhile, researchers believe that this garden was already built during the Iskandar Muda era. Portuguese maps provide information that this garden did not exist in the sixteenth century, while a map of the Netherlands in the nineteenth century before the start of the Dutch Aceh War, also does not depict this garden at all. This research proposes the idea that this garden was likely built during the reign of Iskandar Muda and was lost before the Dutch military aggression to Aceh.